Naqli-Aqli Socio-Cultural Instructional Discourse: Characteristics Analysis - Harison Mohd. Sidek; Tun Nur Afizah Ariff Zainal; Mohd Muzhafar Idrus; Noor Saazai Mat Saad; Hazleena Baharun (Universiti Sains Islam Malaysia, 2024)
The purpose of this study was to analyze the characteristics of an instructional discourse within the realm of the socio-cultural theory with the integration of naqli perspectives. A pre-school teacher and a group of pre-school children participated in the study. Real time non-participant observation, field notes and postobservation of the videotaped of the selected conversation were the methods of data collection for the study. The data were analyzed qualitatively using the coding derived the literature review. The data were categorized in three characteristic themes: the interdependence between social and individual processes, co-construction of knowledge and the use of meaningful and purposeful language. The findings show that the selected instructional conversation reflects the characteristics of discourse within the realm of the socio-cultural theory. The implications of the study are discussed within the context of second language teaching.